DESIGN OF INFORMATION TECHNOLOGY GOVERNANCE IN THE INFORMATION TECHNOLOGY DIVISION OF PT PLN USING THE FRAMEWORK COBIT 2019 - Jennis Tonapa; Erma Suryani (JIKO (Jurnal Informatika dan Komputer), 2023)
In order to support the company's main business objectives, PLN UP3 Manokwari has implemented Information Technology (IT) which is structurally managed and implemented by the information technology division. However, information technology management in the IT division has not yet implemented information technology governance. To support the ongoing management of information technology, the information technology division of PLN UP3 Manokwari still uses the system manually. Manual management of information technology has many risks, this causes the company's main business objectives to not be achieved optimally. The method used in this study refers to the 2019 COBIT framework. From data analysis, it is known that the level of capability of the selected IT governance process in this study is the process in the domain EDM03, APO03, APO12, APO13, BAI01, BAI03, BAI06, BAI07, BAI11 , and DSS05 are mostly still at level 2, while the capability level expected by companies is mostly at level 4. The results of this study are in the form of recommendations for improvements aimed at achieving the expected level of capability by companies and design of IT governance as a reference for the IT Division PT PLN UP3 Manokwari in managing better IT processes to support the achievement of the company's main business objectives.